2008
DOI: 10.1093/brain/awn024
|View full text |Cite
|
Sign up to set email alerts
|

BDNF increases homotypic olivocerebellar reinnervation and associated fine motor and cognitive skill

Abstract: Recovery of complex neural function after injury to the adult CNS is limited by minimal spontaneous axonal regeneration and/or sprouting from remaining pathways. In contrast, the developing CNS displays spontaneous reorganization following lesion, in which uninjured axons can develop new projections to appropriate target neurons and provide partial recovery of complex behaviours. Similar pathways can be induced in the mature CNS, providing models to optimize post-injury recovery of complex neural functions. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
56
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 90 publications
9
56
0
1
Order By: Relevance
“…The effects of selegiline on gait dysfunction and the significantly positive correlation between stride length and pathological characteristics in our study further support the efficacy of the compound on PD-related motor dysfunction. Indeed, several studies have reported that NTFs delay neuronal degeneration and the progression of abnormal gait or walking patterns in rats (46)(47)(48). In patients with PD, intraputaminal GDNF infusion resulted in the significant, sustained improvement of bilateral motor functions, including gait and balance (49).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of selegiline on gait dysfunction and the significantly positive correlation between stride length and pathological characteristics in our study further support the efficacy of the compound on PD-related motor dysfunction. Indeed, several studies have reported that NTFs delay neuronal degeneration and the progression of abnormal gait or walking patterns in rats (46)(47)(48). In patients with PD, intraputaminal GDNF infusion resulted in the significant, sustained improvement of bilateral motor functions, including gait and balance (49).…”
Section: Discussionmentioning
confidence: 99%
“…47) Previous studies showed that BDNF is beneficial for improvement of depression 47) and fine motor and cognitive skills. 48) During cognitive behavior therapy, fatiguerelated cognition is challenged to diminish somatic attributions, improve the sense of control over symptoms, and facilitate behavioral change. Interestingly, a neuroimaging study in CFS patients indicated that cognitive behavior therapy is associated with a reversal of gray matter atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…For LM22A-4, n = 28-57 wells derived from 4 experiments were assessed. *P < 0.05, # P < 0.01, § P < 0.001. been reported to improve motor recovery and increase measures of neuronal remodeling after cortical ischemia (36, 37) and cerebellar pedunculotomy (38). Though BDNF infusion has been reported to have no effect on spatial learning after TBI (39, 40), motor learning was not assessed in those studies.…”
Section: Figurementioning
confidence: 99%